Backgrounds of mineral nutrition of alfalfa agrocenosis and productivity of subsequent crop of field crop rotation - spring wheat variety ‘Eskada 70’on grey forestry soils of the Republic of Tatarstan - F. N. Safiollin; G. S. Minnullin; M. M. Khismatullin; S. V. Sochneva (Зерновое хозяйство России, 2018)
The paper considers the correlation of backgrounds of nutrition and a layer of alfalfa agrocenosis on the sowings of spring wheat variety ‘Eskada 70’ as a subsequent crop of field crop rotation. On the basis of the comparative assessment of the study of grass stand and backgrounds of their mineral nutrition we have worked out specific proposals for production, providing a sufficient balance of humus in low fertile grey forestry soils of Tatarstan and obtaining high qualitative grain of spring wheat on 35 hwt/ha more with 550-650 rubles/hwt of cost price and 800-900 rubles/hwt of market price. It has been proved experimentally that the use of the doses of fertilizer mixtures allows not only form highly productive alfalfa agrocenosis but also control fertility of vast grey forestry soils of the Republic of Tatarstan. The use of the layer of perennial grasses as fallow for spring wheat produced high yields of grain and reduced the need of mineral fertilizers for the sowings.